Tunnel-Proofing the Executive Suite: Transparency, Temptation, and the Design of Executive Compensation - Noe, Thomas H. (Review of Financial Studies, 2009)
This paper considers optimal compensation for a CEO who is entrusted with administering corporate assets honestly. Optimal compensation designs maximize integrity at minimum cost. These designs are very “low powered,” i.e., while specifying a lower bound for performance and increasing pay with performance, they increase compensation at a rapidly decreasing rate. Thus, integrity considerations engender optimal compensation packages that closely resemble the very pervasive 80/120 bonus plans, exactly the sort of compensation that Jensen (2003) argues should compromise integrity. Under optimal designs, expected compensation increases linearly with firm size, and increases in the market/book ratio. Moreover, given optimal compensation, CEO asset diversion is limited to high market-to-book firms that have received negative productivity shocks.